Synthesis and evaluation of the antileishmanial activity of silver compounds containing imidazolidine-2-thione - Espuri, Patrícia Ferreira; dos Reis, Larissa Luiza; de Figueiredo Peloso, Eduardo; Gontijo, Vanessa Silva; Colombo, Fábio Antônio; Nunes, Juliana Barbosa; de Oliveira, Carine Ervolino; De Almeida, Eduardo T.; Silva, Débora E. S. [UNESP]; Bortoletto, Jessica [UNESP]; Segura, Daniel Fonseca [UNESP]; Netto, Adelino V. G. [UNESP]; et al. (Springer Nature, 2019)
Abstract: A new series of silver compounds could be of interest on designing new drugs for the treatment of leishmaniasis. The compounds [Ag(phen)(imzt)]NO3(1), [Ag(phen)(imzt)]CF3SO3(2), [Ag(phen)2](BF4)·H2O (3), [Ag2(imzt)6](NO3)2(4), and imzt have been synthesized and evaluated in vitro for antileishmanial activity against Leishmania. (L.) amazonensis (La) and L. (L.) chagasi (Lc), and two of them were selected for in vivo studies. In addition to investigating the action on Leishmania, their effects on the hydrogen peroxide production and cysteine protease inhibition have also been investigated. As for antileishmanial activity, compound (4) was the most potent against promastigote and amastigote forms of La (IC50 = 4.67 and 1.88 μM, respectively) and Lc (IC50 = 9.35 and 8.05 μM, respectively); and comparable to that of amphotericin B, reference drug. Beside showing excellent activity, it also showed a low toxicity. In the in vivo context, compound (4) reduced the number of amastigotes in the liver and spleen when compared to the untreated group. In evaluating the effect of the compounds on Leishmania, the level of hydrogen peroxide production was maintained between the lag and log phases; however, in the treatment with compound (4) it was possible to observe a reduction of 25.44 and 49.13%, respectively, in the hydrogen peroxide rates when compared to the lag and log phases. It was noticed that the presence of a nitrate ion and imzt in compound (4) was important for the modulation of the antileishmanial activity. Thus, this compound can represent a potentially new drug for the treatment of leishmaniasis. Graphical abstract: [Figure not available: see fulltext.].
Keywords: Biological effects; Leishmania; Silver compounds